Strategi Membangun Kemandirian dan Kesejahteraan Masyarakat Desa: Bukti Dari Gunung Sewu Geopark, Indonesia - Rohmat Junarto; M. Nazir Salim (Tunas Agraria, 2022)
Knowing the successful development process of a region is important to make a benchmark to build a prosperous, advanced and independent society. The existence of the COVID19 virus pandemic situation requires adjustments to all aspects of life, including the existence of culturally independent villages. This study aims to study the innovations of Bejiharjo Village as an adaptation measure and survive the pandemic. This study uses a mix method with a triangulation approach to capture the wealth of rural areas and to describe community creativity in village development. The results showed that from a total of 20 hamlets in one village, they were unique in the form of tourism, creativity-arts, crafts/crafts and culinary arts. There are three hamlets that innovate through ecotourism and edu-tourism, two hamlets that are creative in the field of classical and modern art aesthetics, five hamlets that rely on local culinary arts with raw materials around the environment, 10 other hamlets by making traditions exist. Ecotourism and eco-creation that are based on local capabilities are an alternative to development and contribution to rural economic value. Local wisdom and the use of resources around the environment become the community's collective basis for sustainable village business management. This research crystallizes the steps in responding to the pandemic, namely mapping the potential and activities down to the village level, strengthening the ecotourism and eco-creative sectors, and increasing inclusive community participation. Abstrak Mengetahui keberhasilan atau hambatan dalam proses pembangunan perdesaan adalah penting untuk menjadikannya tolak ukur mewujudkan masyarakat yang sejahtera dan mandiri. Pemberlakuan berbagai kebijakan akibat situasi pandemi COVID-19 meniscayakan masyarakat kehilangan pekerjaan, menderita kemiskinan, kegiatan ekonomi mengalami kontraksi, bahkan berhenti produksi. Penelitian ini bertujuan untuk mempelajari strategi-inovasi yang dilakukan oleh masyarakat Desa Bejiharjo terhadap basis ekonominya sebagai langkah penanggulangan kemiskinan atau pun pandemi. Penelitian ini menggunakan mix method dengan pendekatan triangulasi. Hasil penelitian menunjukkan bahwa ekowisata dan eko-kreatif yang berpijak pada kemampuan lokal mampu memenuhi kebutuhan mendasar masyarakat, yaitu: pangan, papan, dan sandang. Sektor pertanian menjadi basis ekonomi masyarakat desa untuk bertahan dari pandemi, seiring menurunnya pendapatan mereka karena terhentinya kegiatan industri wisata atau pun jasa. Kearifan lokal dan pemanfaatan sumber daya di sekitar lingkungan menjadi basis kolektif masyarakat desa untuk pemulihan dan keberlanjutan pengelolaan usaha desa. Penelitian ini menekankan bahwa pemberdayaan masyarakat melalui kegiatan yang produktif terhadap sumber daya alam dan buatan mampu meningkatkan pendapatan, menjalankan roda perekonomian dan menciptakan kemandirian desa.